2019
DOI: 10.1002/jcp.29132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional lncRNAs based on competing endogenous RNA network in osteoblast differentiation

Abstract: Adult human mesenchymal stem cells have the potential to differentiate into osteoblast, which plays crucial roles in bone regeneration and repair. Some transcriptional factors (TFs), such as BMP-2 and RUNX2, have been demonstrated to control the differentiation processes. It is important to discover more key regulators in osteoblast differentiation. Recently, some studies found long noncoding RNAs (lncRNAs) participating in osteoblast differentiation, such as MALAT1, DANCR, and ANCR. In this study, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…As a kind of noncoding RNA, lncRNA can function as ceRNA and restrain miRNA by lncRNA-miRNA sponge in cancer, cardiovascular disease, and so on [25,26]. Several functional lncRNAs have been demonstrated to influence osteoblast differentiation and OA pathogenesis through lncRNA-miRNA-mRNA ceRNA mechanism [27][28][29][30]. Some lncRNAs can affect the degradation of the extracellular matrix of chondrocytes by functioning as ceRNAs of specific miRNAs and thus participate in the development and progression of OA, such as lncRNAs of HOTTIP, MEG3, and XIST [28,29,31].…”
Section: Lncrna Ighcγ1 Promoted Inflammation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…As a kind of noncoding RNA, lncRNA can function as ceRNA and restrain miRNA by lncRNA-miRNA sponge in cancer, cardiovascular disease, and so on [25,26]. Several functional lncRNAs have been demonstrated to influence osteoblast differentiation and OA pathogenesis through lncRNA-miRNA-mRNA ceRNA mechanism [27][28][29][30]. Some lncRNAs can affect the degradation of the extracellular matrix of chondrocytes by functioning as ceRNAs of specific miRNAs and thus participate in the development and progression of OA, such as lncRNAs of HOTTIP, MEG3, and XIST [28,29,31].…”
Section: Lncrna Ighcγ1 Promoted Inflammation Bymentioning
confidence: 99%
“…Some lncRNAs can affect the degradation of the extracellular matrix of chondrocytes by functioning as ceRNAs of specific miRNAs and thus participate in the development and progression of OA, such as lncRNAs of HOTTIP, MEG3, and XIST [28,29,31]. Some lncRNAs have been well documented to regulate the differentiation of osteoblasts via the lncRNA-miRNA ceRNA network [27]. Besides, Fan et al have found that DANCR can regulate the progression of OA via targeting miR-577 through ceRNA mechanism [32].…”
Section: Lncrna Ighcγ1 Promoted Inflammation Bymentioning
confidence: 99%
“…The lncRNA-associated competing endogenous RNA (ceRNA) network has attracted much attention recently [12,[32][33][34]. Series of records have proved that MALAT1 play a prominent role in cell proliferation, differentiation and angiogenesis by functioning as a ceRNA [40]. One latest study indicates that MALAT1 mediates proliferation and apoptosis of VSMCs by sponging miRNA-124-3p [41].…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al [71] investigated the lncRNA-mRNA crosstalk, by using computational analysis, to realize a network called "osteoblast-differentiation-associated lncRNA-mRNA network" (ODLMN). First, the authors identified lncRNAs and genes differentially expressed in osteogenic differentiation.…”
Section: Bioinformatic Studymentioning
confidence: 99%